2003
DOI: 10.1097/01.lab.0000087622.80751.c5
|View full text |Cite
|
Sign up to set email alerts
|

Nonrandom Chromosomal Numerical Abnormality Predicting Prognosis of Gastric Cancer: A Retrospective Study of 51 Cases Using Pathology Archives

Abstract: SUMMARY:Chromosomal or centromerical numerical abnormality (CNA) is a well-known characteristic of human cancer, but the extensive and specific documentation of CNA in gastric cancer is still sparse, partly because of difficulty in obtaining cytogenetic information. Taking advantage of a recently developed fluorescence in situ hybridization protocol for formalin-fixed paraffin-embedded tissues, we investigated CNA of 51 gastric cancer cases with a panel of 18 chromosome-specific ␣-satellite probes (for chromos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 27 publications
1
28
0
Order By: Relevance
“…Perhaps even more inexplicable according to currently prevailing gene-level models of tumorigenesis are several examples of neoplastic types characterised by multiple numerical chromosome abnormalities without concomitant structural karyotypic changes [21]. FISH studies have shown numerical aberrations, 1, 7, 8, 9, 17, 20, X and Y, to be common in primary gastric cancer [18,[22][23][24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps even more inexplicable according to currently prevailing gene-level models of tumorigenesis are several examples of neoplastic types characterised by multiple numerical chromosome abnormalities without concomitant structural karyotypic changes [21]. FISH studies have shown numerical aberrations, 1, 7, 8, 9, 17, 20, X and Y, to be common in primary gastric cancer [18,[22][23][24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…The relationships of the BAC clones to the SNP probes are summarized in Table 3 and Supplementary Figure S4. Sections (5 mm thick) were cut from fresh-frozen liver cancer and background liver tissues, which were fixed in 80% ethanol for 24 h, embedded in paraffin and arranged in a tissue microarray, and were used for microwaveassisted FISH analysis (Kitayama et al, 2003). Bacterial artificial chromosomes clones were labeled with Alexa 546 and 488 (Molecular Probes, Eugene, OR, USA) by nick translation.…”
Section: Genome Imbalance Mapmentioning
confidence: 99%
“…With regard to centromere enumeration probes, Spectrum Green-labeled CEP10 and Spectrum Orange-labeled CEP1 (Vysis Inc., Downers Grove, IL, USA) were used with differently labeled RP11-79B11 and RP11-89N3; RP11-90B18 and RP11-166J24, respectively. Hybridization and evaluation of the results were performed as described previously with minor modifications (Kitayama et al, 2003). DAPI I (4,6-diamidino-2-phenylindol, 1000 ng/ml; Vysis Inc.) was used for nuclear counterstaining.…”
Section: Genome Imbalance Mapmentioning
confidence: 99%
“…On the other hand, a poor prognosis had been predicted by other genomic lesions, as, for instance, specific p53 mutations [6]. However, scarce information is available on genome-wide molecular analysis of prognostically informative histologic subtypes, because most of the studies published so far are based on broad tumor categories like intestinal and diffuse histotypes [7][8][9][10][11][12] or histologically more descriptive types [13,14], which are themselves of limited prognostic value [15,16], rather than on histologic types specifically designed to predict patient outcome [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%